2017
DOI: 10.1021/acs.cgd.7b01334
|View full text |Cite
|
Sign up to set email alerts
|

Cyclohexanone-Driven Discriminatory Behavior Change of Host Compound (+)-(2R,3R)-TETROL for Isomeric Methylcyclohexanone Guests

Abstract: Using appropriate competition experiments, host compound TETROL [(+)-(2R,3R)-1,1–4,4-tetraphenylbutane-1,2,3,4-tetraol] was revealed to discriminate between the isomeric methylcyclohexanone guests; the host selectivity was in the order 2- ≫ 3- > 4- methylcyclohexanone. Surprisingly, addition of unsubstituted cyclohexanone to these competitions instigated a complete reversal in the host’s preference for the alkylcyclohexanones: a selectivity order of cyclohexanone >4- > 3- > 2-methylcyclohexanone was attained. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…To clarify the difference in the CH−π interactions in the inclusion crystal, we performed Hirshfeld surface analyses for 1 2 · o -xylene, 1 2 · m -xylene, and 1 2 · p -xylene using the CrystalExplorer 17 program . This analysis is useful for evaluating the origin of the packing structure and structure of inclusion complexes constructed by host and guest molecules. Hirshfeld surfaces of a guest molecule in each inclusion crystal are shown in Figure a–c. The two-dimensional fingerprint plots for each Hirshfeld surface, where d e and d i are distances to the nearest atom outside and inside the surface, respectively, are shown in Figure d–f.…”
Section: Resultsmentioning
confidence: 99%
“…To clarify the difference in the CH−π interactions in the inclusion crystal, we performed Hirshfeld surface analyses for 1 2 · o -xylene, 1 2 · m -xylene, and 1 2 · p -xylene using the CrystalExplorer 17 program . This analysis is useful for evaluating the origin of the packing structure and structure of inclusion complexes constructed by host and guest molecules. Hirshfeld surfaces of a guest molecule in each inclusion crystal are shown in Figure a–c. The two-dimensional fingerprint plots for each Hirshfeld surface, where d e and d i are distances to the nearest atom outside and inside the surface, respectively, are shown in Figure d–f.…”
Section: Resultsmentioning
confidence: 99%
“…28–30 Diimide-based macrocycles are expected to be suitable hosts because their oxygen atoms and electron-deficient π–surfaces may engage in the complexation with halocarbons. 31–33 In this study, we showed that three diimide-based macrocycles containing adamantane parts were valuable and accessible hosts for the uptake of several liquid halocarbons. Crystals 1a with iodomethane and 1b with 1,2-dibromoethane were constructed from macrocycle ( 1 ) possessing PMDI units.…”
Section: Introductionmentioning
confidence: 93%
“…The importance of designing and preparing crystalline materials containing liquid organic compounds has become apparent over the last few decades in relation to the structural elucidation of the included guest molecules and the purification and separation of specific compounds from isomeric mixtures through selective molecular recognition by diverse non-covalent interactions. [1][2][3][4][5][6] Macrocyclic compounds are useful hosts for the encapsulation of a wide variety of guest molecules by solution crystallization, which is a simple and low-cost process. [7][8][9] Many molecules including alkanes, alcohols, ethers, amines, and aromatics have been employed as guests.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Competition studies with these guests demonstrated that in the absence of cyclohexanone, the host selectivity order was 2-≫ 3-> 4-methylcyclohexanone; however, as soon as unsubstituted cyclohexanone was added to the competitions, it instigated a complete reversal in this order (cyclohexanone > 4-> 3-> 2-methylcyclohexanones). 11 A dimethoxy derivative of TETROL also displayed host ability and behaved preferentially when recrystallized from mixed xylenes. 12 In the present work, we have assessed its host ability in the presence of guests aniline (ANI), o-, m-and p-toluidine (oTOL, mTOL, and pTOL, respectively), and toluene (TOL) (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…It has the potential to behave as a host material for the separation of the methylpyridines . Cyclohexanone and the isomeric methylcyclohexanones also formed complexes with this host and, surprisingly, the 3- and 4-methyl derivatives were enclathrated as their least stable axial conformers. , Competition studies with these guests demonstrated that in the absence of cyclohexanone, the host selectivity order was 2- ≫ 3- > 4- methylcyclohexanone; however, as soon as unsubstituted cyclohexanone was added to the competitions, it instigated a complete reversal in this order (cyclohexanone > 4- > 3- > 2- methylcyclohexanones) . A dimethoxy derivative of TETROL also displayed host ability and behaved preferentially when recrystallized from mixed xylenes .…”
Section: Introductionmentioning
confidence: 99%